Percutaneous endovascular management of recurrent aneurysm of transplant renal artery anastomosed to internal iliac artery - Umapati N Hegde; Mohan M Rajapurkar; Sishir D Gang; Suhas S Lele (Indian Journal of Urology, 2008)
Aneurysm formation constitutes 0.5 to 1% of all vascular complications in transplant patients. Aneurysms may result from infection, injury during procurement or preservation, faulty suture technique or trauma. Transplant renal artery aneurysm presents with hypertension, graft dysfunction and bleeding. We report a case of percutaneous covered stent-graft for recurrent aneurysm with stenosis of transplant renal artery .To our knowledge this is the first report of successful treatment of transplant renal artery aneurysm with covered stent-graft.